Implementasi Pembelajaran Discovery Learning Berbantuan Role Playing Untuk Meningkatkan Kemampuan Komunikasi Peserta Didik Kelas XI - Fathiya Halimah Nur Sa’diyah; Umi Fatmawati; Bowo Sugiharto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The communication skills of students in the 21st century are crucial for facing global challenges and interacting effectively. Through the discovery learning model supported by role playing, students can hone their communication skills by actively participating in real-life situations, thereby enhancing their confidence andcollaborative abilities. This study aims to improve students' communication skills. The research method used is Classroom Action Research (CAR). Data were collected through observation notes of learning activities and interview results, which were used to reflect on the implementation of the learning model syntax and student responses. The data validity testing technique used in this study is triangulation. The data analysis technique employed in this study is qualitative descriptive analysis. The results indicate that the model and methods of learning used are effective in improving communication skills. Through three cycles of classroom actionresearch, there was a significant improvement in students' verbal communication skills, from 44.99% in the pre-cycle to 79.81% in cycle III, which is classified as high. Non-verbal communication skills also gradually improved, from 40.61% in the pre-cycle to 78.43% in cycle III. This improvement shows that the interventionsmade have a substantial positive impact on the communication skills of the students.